His daughter's prayer - Thorne, Danielle (Love inspired., 2020)
Struggling to keep his antiques store open, single dad Mark Chatham can<U+2019>t turn down his high school sweetheart, Callie Hargrove, when she offers her assistance in the shop. But his daughter is wishing for a mommy, and she<U+2019>s convinced that Callie is the perfect match. As they work to save the business, will their little matchmaker reunite Mark and Callie for good?